Wake up, Donnie: intertextuality and soundtrack in Donnie Darko - SOUSA, Breno José da Silva (2024)
This work aims to analyze some of the possibilities of intertextuality perceptible when comparing texts produced in very different contexts and regarding the soundtrack of a cinematographic adaptation. It concerns identifying the synchronicities of elements composing distinct types of texts and comparing them. Therefore, the objective of this work is to analyze the intertextual aspects between the narrative, characters, and its relationship with the soundtrack, of the three objects of the study: The Bunnyman urban legend; the film Donnie Darko (2001); and the book/script of the same name (2003). The theoretical basis is composed mainly by the ideas of Samoyault (2001), Kristeva (1966), and Bakhtin (1963), concerning intertextuality; Steven Tötösy de Zepetnek (1998) on comparative literature; Fischoff (2005) and Lotman (1978), regarding soundtrack studies. We seek to find elements of communication between the texts (legend and book/script), through their characters and other aspects, and also, if there is the same communication between the soundtrack and scenes from the film, which derived from the texts cited previously. It is concluded that it is possible to perceive intertextuality present in the relationship among the analyzed texts, and that the soundtrack can be used as a tool for making relevant intertextual interventions, regarding the perception of the audience of an audiovisual product.